Study of waterjet propulsion in jet pump system on jet ski / Zahari Awang - Awang, Zahari (Faculty of Mechanical Engineering, Universiti Teknologi MARA, 1998)
The concept of waterjet propulsion dates back to 1661. Toogood and Hayes proposed this form of propulsion. Its use as a basis to manoeuvre small high speed craft. It is only in recent years that the waterjet has been considered for large high speed craft Waterjet propulsion units offer a further dimension to the range of propulsion alternatives. It is tend to use where other propulsion from are rejected for some reason as typical reason of efficiency, caviatation extent, noise or imersion and draught consequently, it can be seen the potential for waterjet application offer optimum performance propulsion. Refers this concept, the pump system in jet ski has been used.